2006
DOI: 10.1143/jjap.45.3587
|View full text |Cite
|
Sign up to set email alerts
|

High-Rate Deposition of Intrinsic Amorphous Silicon Layers for Solar Cells Using Very High Frequency Plasma at Atmospheric Pressure

Abstract: We have investigated the electrical and optical properties of hydrogenated amorphous silicon (a-Si:H) films prepared with extremely high deposition rates using very high frequency (VHF) plasma of gas mixtures containing He, H 2 , and SiH 4 at atmospheric pressure. VHF power is a very important deposition parameter governing the dissociation of SiH 4 molecules and the structural relaxation of the film. When the deposition parameters are optimized, the optical gap of the film can be controlled by the H 2 /SiH 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…1 schematically shows the experimental setup. The reactor used for the experiments is almost the same as that described in our previous reports [4][5][6][8][9][10]. A cylindrical rotary electrode with 200 mm diameter and 150 mm width was placed in the reactor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 schematically shows the experimental setup. The reactor used for the experiments is almost the same as that described in our previous reports [4][5][6][8][9][10]. A cylindrical rotary electrode with 200 mm diameter and 150 mm width was placed in the reactor.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the reduction of substrate heating temperature and the suppression of ion damage of the film are simultaneously expected by utilizing atmospheric pressure plasma. In contrast to the conventional PECVD technique, it is shown that AP-PCVD is a promising technique for the high-rate and low-temperature growth of high-quality functional thin films [4][5][6][7][8][9][10]. The aim of this study is to develop a new technology for the formation of gate oxide layers with good dielectric strength, low interface trap density and low fixed oxide charge density, utilizing the physical and chemical properties of atmospheric pressure plasma.…”
Section: Introductionmentioning
confidence: 99%
“…To date, APG has made remarkable progress in formation techniques; various types of APGs and related applications have been constructed for many purposes. Actually, APG is useful not only for improving the productivity of industrial applications, but also for the synthesis of functional materials such as carbon nanotubes,12–14 diamond‐like carbon,15 ultrahigh‐speed etching,16 silicon oxide nanoparticle deposition,17 and amorphous/crystalline silicon film deposition 18, 19. All have been investigated extensively in the scope of APG.…”
Section: Introductionmentioning
confidence: 99%
“…The HWP-PECVD system used to produce nc-Si:H was based on previously reported designs (see Figure 1) [12][13][14][15][16]. The diameter of the cylindrical rotary electrode was 200 mm, and the width was 100 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we tried to develop a new method of fabricating homogeneous nc-Si:H films. We used a high working pressure plasma-enhanced chemical vapor deposition (HWP-PECVD) system with a cylindrical rotary electrode; this system is superior to conventional PECVD because it has the following features: a high deposition rate as a result of the high partial pressure of the reactive gas and a high plasma density by the very high frequency of 150 MHz; the ability to control the film uniformity because of the homogeneous distribution of reactants by the rotary electrode system; low bombardment damage because of the lower kinetic energy [12][13][14][15][16]. We were able to synthesize nc-Si:H films using HWP-PECVD and even control the crystallinity using a simple parameter, that is, the substrate scan speed.…”
Section: Introductionmentioning
confidence: 99%